Governing large-scale social-ecological systems: Lessons from five cases. Issue 2 (August 2014) - Fleischman, Forrest D.; Ban, Natalie C.; Evans, Louisa S.; Epstein, Graham; Garcia-Lopez, Gustavo; Villamayor-Tomas, Sergio
This paper compares lessons drawn from five case studies of large scale governance of common-pool resources: management of forests in Indonesia, the Great Barrier Reef in Australia, the Rhine River in western Europe, the Ozone layer (i.e. the Montreal Protocol), and the Atlantic Bluefin Tuna (i.e. the International Convention on the Conservation of Atlantic Tuna). The goal is to assess the applicability of Ostrom's design principles for sustainable resource governance to large scale systems, as well as to examine other important variables that may determine success in large scale systems. While we find support for some of Ostrom's design principles (boundaries, monitoring, sanctions, fit to conditions, and conflict resolution mechanisms are all supported), other principles have only moderate to weak support. In particular, recognition of rights to organize and the accountability of monitors to resource users were not supported. We argue that these differences are the result of differences between small and large scale systems. At large scales, other kinds of political dynamics, including the role of scientists and civil society organizations, appear to play key roles. Other variables emphasized in common-pool resource studies, such as levels of dependence on resources, group size, heterogeneity, disturbances, and resource characteristics also receive mixed support, pointing to the need to reinterpret the meaning of common-pool resource theories in order for them to be applicable at larger scales.